THE RELATIONSHIP OF ENGLISH WITH OTHER LANGUAGES - Eshmirzayeva, Nozima Bahodir qizi (Educational Research in Universal Sciences, 2023)
This article discusses the relationship of English with other languages. As the world becomes more connected, the relationship between English and other languages will continue to evolve. English will continue to be a dominant language in many parts of the world, but it will also continue to borrow and be influenced by other languages.